2012
DOI: 10.1159/000336744
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Antibiotic in Adenoidectomy with Partial Tonsillectomy: A Randomized Trial

Abstract: Objectives: To examine potential benefits of perioperative antibiotic therapy in children undergoing adenotonsillotomy. Methods: Adenoidectomy with tonsillotomy was performed in 124 children with obstructive symptoms, aged 5–7 years. Of these, 120 completed the study. Intraoperative intravenous and postoperative oral clindamycin, or placebo for 7 days, were administered. Results: There were significant differences between the groups regarding pain intensity (p < 0.001) and duration (p < 0.05), day of return to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Eight eligible studies [126][127][128][129][130][131][132][133] reported inconclusive pain outcomes with the use of antibiotics. In studies reporting an analgesic effect, two tested antibiotic mouth wash.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Eight eligible studies [126][127][128][129][130][131][132][133] reported inconclusive pain outcomes with the use of antibiotics. In studies reporting an analgesic effect, two tested antibiotic mouth wash.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Nevertheless, the authors considered this finding beneficial, stating that even transient reduction of pain promotes a return to a normal diet, and thus to resuming the activities of daily living [16,41]. Zagóls-ki and Kulisiewicz studied 124 children undergoing tonsillectomy and found that those who received antibiotic prophylaxis experienced reduced intensity and duration of postoperative pain, required fewer additional doses of analgesics and returned earlier to normal physical activities [42]. Moreover, the administration of antibiotic therapy was associated with a lower prevalence and shorter duration of mouth odor, and most importantly, with faster healing and greater satisfaction on the part of the patients' parents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these positive outcomes, the authors highlighted the potential risk of complications related to antibiotic therapy. Therefore, they recommended that patients or their caregivers should be informed of the potential benefits and risks of antibiotic prophylaxis, and should participate in the decision-making process regarding its implementation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Each patient's pharynx was also examined to assess healing and rated on a 5-point scale: 4 - redness and edema of vast regions of pharyngeal mucosa, including the uvula; 3 - edema of the uvula with or without redness and/or edema of anterior pillar mucosa; 2 - redness and edema of peritonsillar tissues excluding the uvula; 1 - redness of anterior pillar mucosa without edema, and 0 - normal mucosa, without redness or edema [20]. Edema of the uvula is an important factor of healing due to its symptoms: pain-causing dysphagia as well as dyspnea [20]. …”
Section: Methodsmentioning
confidence: 99%